Ringer’s Lactate versus Isotonic Saline: The Nasal Irrigation Solution of Choice in Chronic Rhinosinusitis - Gurung, Urmila; Devkota, Anuj; Pokhrel, Shishir; Pradhan, Bibhu (Journal of Institute of Medicine Nepal, 2024)
Introduction Nasal douching is a simple and highly effective treatment option for chronic rhinosinusitis. This study aimed to compare the efficacy of Ringer’s lactate versus isotonic saline for nasal irrigation in treating chronic rhinosinusitis (CRS) with or without polyposis using the SNOT-22 score. Methods This quasi-experimental study was conducted at the Department of ENT and Head & Neck Surgery, Tribhuvan University Teaching Hospital, from September 2020 to November 2021. Seventy-eight patients aged ≥ 16 years with CRS were included in the study. Patients were grouped into either isotonic saline or Ringer’s lactate groups based on the clinician’s preference. Nasal irrigation was prescribed for four weeks. Pre and post-irrigation SNOT-22 scores were analyzed using paired t-test and Student’s t-test. Results A significant improvement in the SNOT-22 scores before and after nasal irrigation was observed in both the Ringer’s lactate (26.76±14.07 vs 14.41±7.92, p<0.001) and isotonic saline groups (24.64±11.12 vs 12.58±6.62, p<0.001). However, the difference in post-nasal irrigation SNOT-22 scores between these groups remained statistically insignificant (p=0.27). Common symptoms such as nasal blockage and thick nasal discharge showed substantial improvement. The most common side effect was fluid pooling in the paranasal sinuses. Conclusion Both isotonic saline and Ringer’s lactate were effective for nasal irrigation in patients suffering from chronic rhinosinusitis, with no significant difference in their efficacy, making either solution a suitable choice for nasal irrigation in the management of the CRS.